EVALUASI TINGKAT KEPUASAN PETANI TERHADAP KINERJA PENYULUH PERTANIAN DI DESA DIRUN KECAMATAN LAMAKNEN KABUPATEN BELU - Bernadina Metboki; Lusia Herlina Lawa Hale; Umbu Joka (Fakultas Pertanian, Universitas Janabadra, 2023)
Extension workers have succeeded in conveying various agricultural innovations to farmers with all their methods so that farmers increase their knowledge and skills and can change farmers’ attitudes to be willing and able to implement new innovations. Agricultural extension workers in village were sent to provide guidance and implementation of field extension activities to 12 to farmer groups and 1 gapoktan. This study aims to determine performance of agricultural instructors, difference in real performance of extension workers according to the extension workers and real performance of extension workers according to farmers as well as level of farmer satisfaction with the performance of agricultural extension workers in the village of Dirun, Lamaknen District, Belu Regency. Population in this study were all members of farmer group, amounting to 315 people from 12 farmer groups with determination of sample using slovin method in order to obtain a research sample of 38 people. Data collection methods used in this study are: survey methods, interviews, primary data, secondary data. Data analysis used in this reseach is descriptive qualitative analisys and likert scale analisys. Results of qualitative descriptive analisys show that average real performance of agricultural extension workers in Dirun village is 40.1, meaning that agricultural instructor’s performance in Dirun village is in Yes category. Results of likert scale analisys show that farmer’s satisfaction with performance of agricultural instructors in Context, Input, Process and Product metodhs is categorized as quite satisfied. Results of average difference test show that there is a difference in real performance of extension workers between farmers and extension workers, farmers consider that performance of extension workers in Dirun village has not been carried out optimally, while extension workers on duty feel that they are doing has been done as much as possible.INTISARIPenyuluh telah berhasil menyampaikan berbagai inovasi pertanian kepada petani dengan segala metodenya sehingga para petani meningkat pengetahuan dan ketrampilan serta dapat mengubah sikap petani menjadi mau dan mampu menerapkan inovasi baru. Penyuluh pertanian di Desa Dirun melakukan pembinaan dan pelaksanaan penyuluhan lapangan pada 12 kelompok tani dan 1 gapoktan. Penelitian ini bertujuan untuk mengetahui kinerja penyuluh pertanian, perbedaan kinerja riil penyuluh menurut penyuluh dan kinerja riil penyuluh menurut petani serta tingkat kepuasan petani terhadap kinerja penyuluh pertanian di desa Dirun kecamatan Lamaknen Kabupaten Belu. Populasi dalam penelitian ini adalah keseluruhan anggota kelompok tani berjumlah 315 orang dari 12 kelompok tani dengan penentuan sampel menggunakan metode slovin sehingga diperoleh sampel 38 orang. Metode pengumpulan data dalam penelitian ini adalah, metode survey, wawancara, data primer, sekunder. Analisis data dalam penelitian ini menggunakan analisis deskriptif kualitatif dan skala likert. Hasil menunjukkan bahwa rata-rata kinerja riil penyuluh pertanian di Desa Dirun adalah 40,1 artinya kinerja penyuluh pertanian di Desa Dirun dalam kategori Ya. Hasil analisis skala likert menunjukkan bahwa kepuasan petani terhadap kinerja penyuluh pertanian dalam metode context, input, process dan product tergolong dalam kategori cukup puas. Hasil analisis uji beda rata menunjukkan bahwa terdapat perbedaan kinerja riil penyuluh antara petani dan penyuluh, petani menilai bahwa kinerja penyuluh belum dilakukan secara maksimal, sementara penyuluh yang bertugas merasa bahwa apa yang mereka kerjakan sudah dilakukan semaksimal mungkin.